Characteristics of Decedents With COVID-19–Related Mortality in Kentucky, July 1–August 13, 2021. (May 2023) - Cavanaugh, Alyson M.; Raparti, Likhita; Bhurgri, Mishaal; Herrington, Amy; Holladay, Claire; Arora, Vaneet; Spicer, Kevin B.; Thoroughman, Douglas A.; Winter, Kathleen
Objective: Although vaccination reduces the risk of severe COVID-19, fatal COVID-19 cases after vaccination can occur. We examined the characteristics of decedents with COVID-19–related mortality to help inform discussions about vaccination, boosters, and mitigation strategies. Methods: We examined COVID-19–related deaths in Kentucky resulting from infections occurring from July 1 through August 13, 2021. We used records from case investigations, medical records, the Kentucky Health Information Exchange, and the Kentucky Immunization Registry to determine demographic information, vaccination status, and underlying health conditions, including calculation of the Charlson Comorbidity Index (CCI). We calculated mortality incidence rates by vaccination status by using data for unvaccinated and fully vaccinated populations in Kentucky as of July 1, 2021. Results: In total, 777 COVID-19–related deaths occurred in Kentucky during the study period; 592 (76.2%) occurred among unvaccinated people. Compared with unvaccinated decedents, fully vaccinated decedents were older (median age, 77 vs 65 years; P  < .001), had higher comorbidity levels (median CCI, 3 vs 1; P  < .001), and were more likely to have immunocompromised health status (26.4% vs 16.0%; P  = .003). Diabetes, hypertension, heart disease, and chronic lung disease were more common among vaccinated decedents than among unvaccinated decedents. Unvaccinated adults had a significantly higher risk of death than fully vaccinated adults (incidence rate ratio for age 20-49 years: 20.5 [95% CI, 6.5-64.8]; 50-64 years: 14.6 [95% CI, 9.4-22.7]; ≥65 years: 10.2 [95% CI, 8.3-12.4]). Conclusions: Immunocompromised health status, older age, and higher comorbidity were prevalent among fully vaccinated decedents, suggesting adults with these characteristics may benefit from additional protection strategies. Further understanding of the protection of additional and booster doses is needed.